Penatalaksanaan Batuk Efektif Akibat Tuberkulosis Paru - Irpan Ali Rahman (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Tuberculosis is a public health problem around the world, with Indonesia in particular being the second leading cause of death from infectious diseases. Objective: Carry out comprehensive nursing care to clients experiencing respiratory system disorders due to Pulmonary TB with effective cough interventions. Method: The design of the study uses a case study, which aims to describe the phenomenon with a nursing care approach. Results: Showing clients said frequent coughs at night, coughing up phlegm, and difficulty removing phlegm are the causes of this Pulmonary TB results in primary infection of the alveoli resulting in increased secretion production resulting in ineffective airway clearance problems. Conclusion: Optimization of airway management in pulmonary tuberculosis nursing care with airway clearance is not effective